1992
DOI: 10.1002/mrc.1260300802
|View full text |Cite
|
Sign up to set email alerts
|

High‐field NMR study of the tautomers resulting from the condensation of 2‐methylindole and phenalenone in the presence of p‐toluenesulphonic acid

Abstract: As phenalene is an alternant hydrocarbon it is oxidized very easily to phenalenone, which condenses with various nitrogen nucleophiles in the presence of p‐toluenesulphonic acid. 2‐Methylindolylphenalene is obtained with 2‐ methylindole, together with other products. This product is a mixture of five tautomers in equilibrium, and these were analysed by homo‐ and heteronuclear two‐dimensional high‐field NMR (500 MHz) spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…42 Various features have been suggested to determine this ratio, such as the relative geometries of the radical pairs required for the disproportionation and the recombination reactions and the reorientation of the radicals in the pair. 42,46 There exists a distinct difference between k RD /k RC for the self-reaction of alkyl radicals 51 and for hydroaromatic (benzylic type) radicals. For example, the k RD /k RC (on a per hydrogen basis and around 330 K) changes from 0.3 (tert-butyl) to 0.0045 (cumyl) which cannot be explained on the basis of geometry or thermodyamic consideration.…”
Section: Scheme 3 Dehydrogenation Of Some Linear Dihydroaromaticsmentioning
confidence: 99%
See 2 more Smart Citations
“…42 Various features have been suggested to determine this ratio, such as the relative geometries of the radical pairs required for the disproportionation and the recombination reactions and the reorientation of the radicals in the pair. 42,46 There exists a distinct difference between k RD /k RC for the self-reaction of alkyl radicals 51 and for hydroaromatic (benzylic type) radicals. For example, the k RD /k RC (on a per hydrogen basis and around 330 K) changes from 0.3 (tert-butyl) to 0.0045 (cumyl) which cannot be explained on the basis of geometry or thermodyamic consideration.…”
Section: Scheme 3 Dehydrogenation Of Some Linear Dihydroaromaticsmentioning
confidence: 99%
“…The various tautomers of 1-methylphenalene have been observed in a NMR study at 298 K. 51 It has been hypothesized that the tautomerization proceeds through a RRD mechanism. 52 The migration of the double bond in (the model) phenalene sets in with a RRD reaction between two phenalene molecules (Scheme 9).…”
Section: Scheme 3 Dehydrogenation Of Some Linear Dihydroaromaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Phenalene 6, the hydrogenated phenalenyl, undergoes six-fold tautomerization (Scheme 2) owing to the hydrogen shift of the benzylic-allylic hydrogen, 5 according to NMR evidence. 6 Inspired by these phenomena, we proposed that the phenalenyl s-dimers undergo six-fold sigmatropic rearrangements by breaking and forming the inter-phenalenyl CC s-bond that is the counterpart of the C(sp 3 )-H bond in phenalene. However, such s-bond shift has not been observed because most of the experimentally isolated phenalenyl derivatives exist in the form of p-dimeric structures.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Phenalene, the precursor of the phenalenyl radical, has been proposed to undergo a six-fold tautomerism as described in Scheme 1, in which the benzylic-allylic hydrogen transfer reactions are hypothesized to occur through an unimolecular process. 6 NMR spectroscopy studies 7 showed that the reactions designed to obtain 1-alkyl-phenalenes, as a result, yielded a mixture of five kinds of isomers indicating that hydrogen transfer occurs 8 in solution. However, the mechanism of this reaction has not been discussed in the literature.…”
mentioning
confidence: 99%